Effect of Thermal Bridges of Different External Wall Types on the Thermal Performance of Residential Building Envelope in a Hot Climate - Hameed Al-Awadi; Ali Alajmi; Hosny Abou-Ziyan (Buildings, 2022)
In this paper, the thermal performance of residential building envelopes including thermal bridges (TBs) in a hot climate, using four different exterior wall types, is modelled and assessed. TBs at the junctions between columns and walls and between walls and slabs of the ground floor, roof, and intermediate floors are considered. The tested wall types are classical (two layers of cement blocks with insulation in between), autoclaved aerated concrete bearing (AAC-B), AAC column and beam (AAC-CB), and exterior insulation and finish system (EIFS). The results indicated that thermal bridges have a considerable effect and determine the best external wall type which was the EIFS that has a continuous exterior insulation. EIFS proved to reduce the heat transmission with the outdoor environment for residential buildings by 101.8, 51.2, and 13.9% than the AAC-CB, AAC-B, and classical walls, respectively. Thermal bridges effect on the building envelope using the EIFS is insignificant as the thermal resistance of the envelope and wall differs by less than 1% for small areas. The overall heat transfer coefficients for small buildings are larger than those for large buildings by 8–26%. As the number of intermediate floors increases from 1 to 50, the envelope overall heat transfer coefficient increases by 4.5% for the EIFS, 14.1% for classical, and 19.5% for AAC-CB walls. The AAC-CB, as the common practice wall structure in many hot climate countries, has the lowest performance among the tested wall types.